Assimilation of Satellite-Based Snow Cover and Freeze/Thaw Observations Over High Mountain Asia - Xue, Yuan; Houser, Paul R.; Maggioni, Viviana; Mei, Yiwen; Kumar, Sujay V.; Yoon, Yeosang (Frontiers in Earth Science, 2019)
Towards qualifying hydrologic changes in the High Mountain Asia (HMA) region, this study explores the use of a hyper-resolution (1 km) land data assimilation (DA) framework developed within the NASA Land Information System using the Noah Multi-parameterization Land Surface Model (Noah-MP) forced by the meteorological boundary conditions from Modern-Era Retrospective analysis for Research and Applications, Version 2 data. Two different sets of DA experiments are conducted: 1) the assimilation of satellite-derived snow cover map (MOD10A1), and 2) the assimilation of NASA MEaSUREs landscape freeze/thaw product from 2007 to 2008. The performance of the snow cover assimilation is evaluated via comparisons with available remote sensing based snow water equivalent product and ground-based snow depth measurements. For example, in the comparison against ground-based snow depth measurements, the majority of the stations (13 out of 14) shows slightly improved goodness-of-fit statistics as a result of the snow DA, but only four are statistically significant. In addition, comparisons to the satellite-based land surface temperature products (MOD11A1 and MYD11A1) show that freeze/thaw DA yields improvements (at certain grid cells) of up to 0.58 K in the root-mean-square error (RMSE) and 0.77 K in the absolute bias (relative to model-only simulations). In the comparison against three ground-based soil temperature measurements along the Himalayas, the bias and the RMSE in the 0 - 10 cm soil temperature are reduced (on average) by 10% and 7%, respectively. The improvements in the top-layer of soil estimates also propagate through the deeper soil layers, where the bias and the RMSE in the 10 cm - 40 cm soil temperature are reduced (on average) by 9% and 6%, respectively. However, no statistically significant skill differences are observed for the freeze/thaw DA system in the comparisons against ground-based surface temperature measurements at mid-to-low altitude. Therefore, the two proposed DA schemes show the potential of improving the predictability of snow mass, surface temperature, and soil temperature states across HMA, but more ground-based measurements are still required, especially at high-altitudes, in order to document a more statistically significant improvement as a result of the two DA schemes.